2021
DOI: 10.1016/j.omto.2021.08.001
|View full text |Cite
|
Sign up to set email alerts
|

miR-1207-5p suppresses laryngeal squamous cell carcinoma progression by downregulating SKA3 and inhibiting epithelial-mesenchymal transition

Abstract: Laryngeal squamous cell carcinoma (LSCC) is the second most common head and neck cancer. Previously, we discovered that miR-1207-5p was downregulated in LSCC. In this study, the clinical significance, function, and mechanism of miR-1207-5p in LSCC were investigated. Downregulation of miR-1207-5p was found to be strongly linked to the malignant progression of LSCC. Functional studies revealed that miR-1207-5p upregulation suppressed LSCC cell proliferation, invasion, migration, and xenograft tumor growth. Bioin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
(64 reference statements)
1
6
0
Order By: Relevance
“…Western blot analysis showed that elevated SKA3 expression is significantly and positively associated with the increased expression of p-Rb, E2F1, CDK4, cyclin D1, CDK2, cyclin E2, and p-Akt in HeLa cells ( 25 ). In addition, SKA3 knockdown inhibited epithelial–mesenchymal transition ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis showed that elevated SKA3 expression is significantly and positively associated with the increased expression of p-Rb, E2F1, CDK4, cyclin D1, CDK2, cyclin E2, and p-Akt in HeLa cells ( 25 ). In addition, SKA3 knockdown inhibited epithelial–mesenchymal transition ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation was assessed using the EdU staining kit (RiboBio, Guangzhou, China) according to the manufacturer’s protocol. Trans-well migration and invasion assays were performed as previously described with modification ( 27 ). Briefly, for the migration assay, cells were seeded in 24-well trans-well plates (Falcon, USA) with a density of 1 × 10 6 cells per well in 100 µL of serum-free media.…”
Section: Methodsmentioning
confidence: 99%
“…5 C). In addition, downregulation of miR-1207-5p was found to be strongly linked to the malignant progression of LSCC while miR-1207-5p upregulation suppressed LSCC cell proliferation, invasion, migration, and xenograft tumor growth 74 . Mechanistic studies revealed that miR-1207-5p primarily inhibited SKA3’s activation of PLK1 and the PI3K/Akt signaling pathway to prevent the growth of cancer cells.…”
Section: Role Of Ska3 In Human Cancermentioning
confidence: 97%